Explaining rising income inequality in Germany, 1991-2010 - Schmid, Kai Daniel; Stein, Ulrike (Berlin, 2013)
"In Germany, inequality of net equivalized income increased noticeably in the first half of the new millennium. We aim to identify the main drivers of this rise in income inequality since the early 1990s. We provide a broad overview of the circumstances under which inequality evolved, i.e. which changes in the German economy are most likely to provide an explanation for changes in income concentration. To explain the development of the distribution of net equivalized income we analyze changes in the distribution of market income as well as shifts in the effectiveness of public redistribution mechanisms. We find that cyclical and structural changes in the labor market, the increasing relevance of capital income as well as the decreasing effectiveness of the public mechanisms of income redistribution are the main explanatory factors for the development of income inequality. In addition to this, we discuss several issues that are of high relevance for the distribution of economic resources but are not directly covered in the analysis of net equivalized income. Most significantly, the design of the tax and social security contributions burden as well as the rising relevance of value-added taxes have exhibited negative redistributive effects for low income households."